Advances in polymer coated textiles - Akovali, Güneri (Smithers Rapra Technology Ltd., 2012)
An up-to-date summary of the technical textile industry, considering the passage from conventional to emerging technologies. It discusses the criteria for selection of coating and textile and summarises the manufacturing basics of the system. It explores a range of emerging technologies, including smart, intelligent and nanostructured applications, alongside the testing and quality control methods of such systems. A must for textile and polymer technologists, engineers, scientists and students.
Keywords: Coated fabrics.; Textile fabrics.; Polymers.; elektronické knihy; electronic books